Development of German-Language Audio Media for Indonesian Folk Tales as an Alternative for Learning Hörverstehen in the Context of Deutsch als Fremdsprache (DaF) at Malang State University - Hanum Dinda Ayu Fardila; Desti Nur Aini (Universitas Negeri Malang, 2025)
This study aims to develop German-language audio media based on Indonesian folk tales as an alternative medium for teaching listening comprehension (Hörverstehen) in Deutsch als Fremdsprache (DaF) at Malang State University. The development employed the ADDIE model, encompassing analysis, design, development, implementation, and evaluation. Preliminary analysis revealed that students experienced difficulties in understanding German audio materials due to fast speech rates, complex vocabulary, and a lack of engaging, contextual media. The folk tale Malin Kundang was selected for its cultural relevance and familiarity. The script was adapted into German using a dramatic narrative style suitable for A2–B1 levels and presented in dialogic form. Audio production utilized AI-based text-to-speech technology (ElevenLabs), complemented by traditional music and edited using CapCut. Expert validation and trials involving 15 students indicated that the media was of very good quality and effective after minor revisions. Formative evaluation showed that the media enhances engagement and supports listening comprehension, despite limitations in AI vocal expressiveness.